ERIC EFFIONG’S IDENTITY CONSTRUCTION IN SEX EDUCATION (PERcursos Linguísticos, 2020)
The British TV series Sex Education has raised discussions on sexuality, especially on issues concerning homosexuality and the challenges faced by LGBTQ+ community, all immersed in a predominantly heteronormative world. Different forces move the characters of this series back and forth and Eric Effiong, a black homosexual teenager whose parents are protestant, goes through significant behavioral changes due to a trauma caused by prejudice. In this article, we aim to present Eric Effiong’s identity construction, built upon his viewpoint about himself as well as upon other characters’ viewpoints. Our research is situated within the area of Applied Linguistics and based on the theoretical principles of the Bakhtin Circle (2011, 2015), Butler (2003), Louro (2000), and Hall (2006), with the purpose of discussing the concepts of centrifugal and centripetal forces, body, sexuality and identity. This interpretive qualitative study examines both Eric Effiong’s utterances and other characters’ utterances. The preliminary findings lead to multifold identities for Eric Effiong.